The Effectiveness of the SP4N-LAPOR! as a National Public Service Complaint Management Application - Premaiswari, Ni Made Widya; Siregar, Ramlan; Ghazali, Rusman (Magister Ilmu Administrasi Publik, 2024)
The implementation of the National Public Service Complaint Management System-Online Aspiration and Complaints Service (or Sistem Pengelolaan Pengaduan Pelayanan Publik Nasional- Layanan Aspirasi dan Pengaduan Online a.k.a SP4N-LAPOR!) as a national public service complaint management application is still facing several problems. Ministry of State Apparatus Empowerment and Bureaucratic Reform (or Kementerian Pendayagunaan Aparatur Negara dan Reformasi Birokrasi a.k.a KemenPANRB) as a national admin of the SP4N-LAPOR! carries out monitoring and evaluation duties at the national level and forwards the reports to each government agency, thus playing an essential role in the effectiveness of SP4N-LAPOR!. This research aims to determine the effectiveness of implementing public service complaint management in the SP4N-LAPOR! by KemenPANRB in 2021. Qualitative and descriptive approaches as well as interview observation and documentation were used to collect data. The findings in the research show that the SP4N-LAPOR! has been planned and arranged according to applicable regulations. However, in practice, the implementation of SP4N-LAPOR! has not been optimal due to several factors: commitment, coordination, technical and operational capabilities, technology, and community involvement.